Development and evaluation of Alternaria blight tolerant lines in Indian mustard (Brassica juncea) (Journal of Oilseed Brassica, 2026)
The present study was aimed to evaluate and develop Alternaria blight tolerant lines in Indian mustard [Brassica juncea (L.) Czern & Coss.]. A total of 14 Alternaria blight tolerant lines were selected from 214 lines in F8 generation. Amongst the selected lines, DRMR-2803, DRMR-2805 and DRMR-2806 showed the least per cent mean disease severity values of 11.4, 10.4 and 9.4, respectively. However, only DRMR-2805 exhibited seed yield/plant higher than the check variety Varuna. Per se performance of selected lines, evaluated for three consecutive years (2010-13), varied considerably for most yield parameters. The most pronounced range was obtained for plant height (203.7 - 264.5 cm), siliquae on main shoot (36.4 - 61.7), main shoot length (30.6 - 81.3 cm), and seed yield per plant (5.4 - 39.7g); number of primary branches/plant (7.1 -12.2) siliqua length (3.0 - 4.5 cm), number of seeds/siliqua (12.4 - 15.6), 1000 seed weight (2.3 - 5.4g), and % oil content (39.6 - 41.6) exhibited narrow range of variation. RAPD analysis of selected Alternaria blight tolerant lines, along with tolerant, (PHR-2 and PAB- 9511), and susceptible (Varuna) checks, clearly distinguished the individual lines to their available pedigree data. Highly promising tolerant lines identified in the present study may be used as potential donors for transferring Alternaria blight tolerance in high yielding mustard varieties. The advanced Alternaria blight tolerant breeding line DRMR-2805 showing seed yield/plant almost at par with check variety Varuna must be released as a variety after multi-location testing.